Developing a comprehensive methodology for evaluating economic impacts of floods in Canada, Mexico and the United States. (November 2020) - Adeel, Zafar; Alarcón, Ana María; Bakkensen, Laura; Franco, Ernesto; Garfin, Gregg M.; McPherson, Renee A.; Méndez, Karla; Roudaut, Marie Blanche; Saffari, Hirmand; Wen, Xin
Abstract: Assessing the true economic costs of floods is central to addressing their impacts, allocating adequate resources for monitoring and preparedness, assessing their changes over time, and building resilient communities. Considerable variability exists in the choice and implementation of methods used in Canada, Mexico, and the United States at national and sub-national levels for estimating the direct damages and indirect losses caused by floods. This inter- and intra-national variability leads to information gaps when prioritizing development investments, for example, for infrastructure renewal, institutional development, or community enhancements. This paper provides an overview of the range of approaches used in the three countries and analyzes their strengths and weaknesses. It then presents a proposed comprehensive and inclusive methodology that has been developed in close collaboration with a range of stakeholders and domain experts. This methodology builds on existing approaches and offers a comprehensive accounting of costs related to flooding. We offer insights into potential challenges for implementing this methodology across the three countries, particularly related to data availability, access, quality, and spatial coverage. We recommend enhanced gathering data and metadata, and storing it in an information warehouse for their timely dissemination. We also identify the need for further investigation into the definition for "extreme flooding" that incorporates hydrological, societal and economic thresholds, in collaboration between government agencies and the research community.